Utilisation de l’Azolla comme biofertilisant sur deux variétés de tomate (Solanum lycopersicum L.) - Menad, Aya; Cheurfi, Ilhem (My University, 2025)
The use of biofertilizers in agriculture has become an environmental and economic reality. This study evaluated the effect of Azolla, alone or combined with NPK, on two tomato varieties (Ksi-Rosa and Sereen F1). The results obtained showed that Azolla as a biofertilizer improved vegetative growth and productivity of tomatoes. The Azolla + NPK mixture gave the best results for the majority of the parameters studied (stem length, number of flowers, weight and fruit yield), thus confirming a synergy between the rapid action of mineral fertilizers and the lasting effect of the biofertilizer. The Sereen F1 variety responded better to the combination than Ksi-Rosa, producing higher yields. Overall, the use of Azolla appears to be an ecological and sustainable alternative, capable of reducing dependence on chemical fertilizers while maintaining high agricultural productivity.
Keywords: Azolla, biofertilizer, NPK, tomato, growth, yield